2000
DOI: 10.1007/s002510050017
|View full text |Cite
|
Sign up to set email alerts
|

Independent evolution of Toll and related genes in insects and mammals

Abstract: Toll and Toll-related proteins play an important role in antibacterial innate immunity in insect, plants, and mammals. We present the first comprehensive phylogenetic analyses of Toll-related genes from both insects and mammals. Drosophila melanogaster contains Toll and a highly homologous gene, Tehao. The protein, Dm Tehao, comprises 795 amino acid residues and its cytoplasmic domain shares a striking 61% identity with Dm Toll. Two Toll homologues were found in another dipteran of medical importance, Anophele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(45 citation statements)
references
References 29 publications
4
39
0
2
Order By: Relevance
“…In more recent studies, Toll-like receptors were found to be responsible in nonadaptive, innate resistance to microbes. These receptors are shared between arthropods (including mosquitoes) and vertebrates (193). Furthermore, although little is known about the molecules in immune responses induced in arthropod cells, activation of several genes encoding anti-microbial peptides was confirmed in mosquito cells infected with WNV (213).…”
Section: Pathology and Resistance To Viral Infectionmentioning
confidence: 95%
“…In more recent studies, Toll-like receptors were found to be responsible in nonadaptive, innate resistance to microbes. These receptors are shared between arthropods (including mosquitoes) and vertebrates (193). Furthermore, although little is known about the molecules in immune responses induced in arthropod cells, activation of several genes encoding anti-microbial peptides was confirmed in mosquito cells infected with WNV (213).…”
Section: Pathology and Resistance To Viral Infectionmentioning
confidence: 95%
“…1A). The eight Drosophila Toll-related proteins share higher similarity between them than with any mammalian TLR, suggesting that these two groups of proteins have evolved independently (11,20). The Drosophila Tolls fall into several subsets, as illustrated in Fig.…”
Section: A Family Of Toll Receptors In Drosophilamentioning
confidence: 99%
“…Toll-5 and Toll-8 were both initially identified as genomic clones sequenced by Berkeley Drosophila Genome Project and have been recently described under the names of tehao (GenBank accession no. AF140019) (20) and Tollo (GenBank accession no. AF204158), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…These signaling pathways regulate expression of antimicrobial peptides that are active against Gram-positive and Gramnegative bacteria, as well as fungi (Anderson, 2000;Tauszig et al, 2000;Hoffmann and Reichhart, 2002;Rutschmann et al, 2002). A large family of Toll-related receptor genes has been identified from a number of insects including Toll, (Toll-3 to -9), 18-wheeler, Trex, Tollo and Tehao (Eldon et al, 1994;Williams et al, 1997;Luo and Zheng, 2000;Luna et al, 2002;Bilak et al, 2003). Toll-related receptors are a group of evolutionarily conserved proteins with diverse biological functions.…”
Section: Introductionmentioning
confidence: 99%